2009
DOI: 10.1177/0011128709333725
|View full text |Cite
|
Sign up to set email alerts
|

Offender Perceptions of Graduated Sanctions

Abstract: Finding credible alternatives to revocation for offenders who violate the conditions of their community supervision has emerged as a salient issue in the corrections field. A number of jurisdictions have turned to graduated sanctions as an alternative to revocation. This study addresses one of the major gaps in the research on graduated sanctions by examining perceptions of graduated sanction severity through the administration of surveys to offenders under active supervision. Survey results revealed several i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 17 publications
3
25
1
Order By: Relevance
“…Prior research, although it was conducted with adult offenders who were predominately White, revealed that offenders view treatment‐oriented sanctions as more punitive than other graduated sanctions (Wodahl, Ogle, Kadleck, and Gerow, ; see also Petersilia and Deschenes, ; Wood and Grasmick, ). However, younger and more educated offenders viewed alternative sanctions, including treatment, less harshly, with high‐school graduates willing to endure almost twice as many days of inpatient treatment to avoid a 1‐day extension of the jail sanction (Wodahl et al., ). Future research should examine juvenile offender perceptions of the graduated sanctions options in Florida's disposition matrix and how these perceptions vary based on individual characteristics.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Prior research, although it was conducted with adult offenders who were predominately White, revealed that offenders view treatment‐oriented sanctions as more punitive than other graduated sanctions (Wodahl, Ogle, Kadleck, and Gerow, ; see also Petersilia and Deschenes, ; Wood and Grasmick, ). However, younger and more educated offenders viewed alternative sanctions, including treatment, less harshly, with high‐school graduates willing to endure almost twice as many days of inpatient treatment to avoid a 1‐day extension of the jail sanction (Wodahl et al., ). Future research should examine juvenile offender perceptions of the graduated sanctions options in Florida's disposition matrix and how these perceptions vary based on individual characteristics.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Graduated sanctions are engaged as a method of deterrence that is used before revoking the probation or parole agreement. Although they have become somewhat common in correctional practice, research has found mixed evidence of their effectiveness, particularly among different populations (i.e., drug offenders, juveniles; Guastaferro & Daigle, 2012;Johnson, Lanza-Kaduce, & Woolard, 2011; see also Wodahl, Ogle, Kadleck, & Gerow, 2009). It would be important in future studies to discover where officers learn the method of graduated sanctions-they may be trained to use it, it may be in their agency policies, or it may be an implicit strategy they have found to be effective through experience.…”
Section: Discussionmentioning
confidence: 99%
“…Polakow and Doctor (1974) found that negative behaviors, like arrest and technical violations, were reduced and positive behaviors, like maintaining employment, increased when probationers received reductions in their probation sentences as a result of meeting case plan objectives. In addition, Wodahl and colleagues (2013) studied the impact of both incentives and sanctions on probationers and parolees supervised through a Wyoming ISP program. A range of incentives were used by supervision officers, such as verbal praise, removal from electronic monitoring, and reductions in total supervision time.…”
Section: Prior Research On Sanctions and Incentives In Community Supementioning
confidence: 99%
“…As the goal of this article is to examine the effects of incentives, praise, sanctions, and reprimands on criminal offending and substance use across time, we use a cross-lagged dynamic panel model (Allison, 2015;williams et al, 2016). Although cross-lagged dynamic panel models are not new to the field of criminology, we use a version of this method outlined by Allison (2015) and williams et al (2016) for a variety of reasons (see .…”
Section: Analytic Strategymentioning
confidence: 99%
See 1 more Smart Citation